Difficulty of Mathematics teacher competence in applying curriculum online - Jitu Halomoan Lumbantoruan Halomoan (Asian Journal of Educational Technology, 2022)
The study aims to analyze the readiness and difficulty of online learning. Survey of the Ministry of Education 2020, 58% ineffective learning process, 38% lack of guidance, 35% poor communication, 62% need internet access, 59.5% object to homework. Research aims; 1)knowing the four teacher competency readiness when online, 2) knowing the location of the difficulty of teacher competence in the online process, 3) knowing the assessment method used. Method by presenting data, reduction and conclusion. The results of the analysis, 1) The material provided does not match the initial ability standards, the books provided do not make it easier for students, the teacher has difficulties in writing symbols. Professional competency assessment is 62%, pedagogic, the teacher does not have a module as a learning aid tool, the teacher has difficulty writing integral symbols, logarithms, matrices and mathematical induction on google meet. 2) The difficulty of the teacher when operating the google meet media, the teacher does not master how to write symbols, the difficulty of proving, the difficulty of expressing the concept, the difficulty of the internet network, the difficulty of correcting the homework, the difficulty of applying the method. Rating 45% disagree with the pedagogic, the book given the concept is too difficult, the impact is that understanding does not develop and is only accepting answers from the teacher without any active interaction. 3) 60% disagree with the assessment method, the material being tested is more difficult than what is taught, as a result the learning outcomes are not as expected. In conclusion, students expect the teacher to compile their own material in the form of a module and pour models, methods, strategies and make assessment indicators in the module.